Manifestations, diagnosis and treatment of disseminated Kaposi's sarcoma: A literature review (Research, Society and Development, 2024)
Kaposi's sarcoma is a multifocal mesenchymal neoplasm caused by human herpesvirus type 8, which has an incidence associated with Human Acquired Immunodeficiency Syndrome and is one of the AIDS-defining diseases. It presents neo-angiogenesis, inflammatory infiltration, vascular lesions, and endothelial involvement, associated with more frequent mucocutaneous involvement and possible involvement of viscera and lymph nodes. It has a more aggressive presentation related to human immunodeficiency syndrome, with the potential participation of the gastrointestinal tract, lungs, oral mucosa, and genitalia. The clinical history and the appearance of characteristic skin lesions, with specific histopathological findings on biopsy, are the basis for the diagnosis. In the therapeutic approach for cases of association between Kaposi's sarcoma and AIDS, antiretroviral therapy is used for all patients, regardless of CD4 count, reserving chemotherapy for patients with advanced-stage disease, or in cases of evidence of rapid progression. This study aims to present a narrative review of the literature that seeks to broaden the debate on the subject from the perspective of studying disseminated Kaposi's sarcoma after initiating antiretroviral therapy. The advent of antiretroviral therapy in controlling HIV infection can lead to a significant reduction in the incidence and aggressiveness of Kaposi's sarcoma, and paradoxically, ART itself also participates in the process of manifestation of the disease, contextualizing the Immune Reconstitution Inflammatory Syndrome.